Zmiany zręczności manualnej w rozwoju osobniczym - Nowicki, Grzegorz (Polskie Towarzystwo Antropologiczne, 1988)
CHANGES IN MANUAL DEXTERITY IN ONTOGENESIS. 8,509 males and 9,680 females were examined to discover the changes'in manual dexterity during ontogenesis. The research was carried out in the Bydgoskie, Toruńskie, and , Włocławskie1 voivodships.
CHANGES IN MANUAL DEXTERITY IN ONTOGENESIS